(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We combine the concept of having multiple fixed points for a mapping with the approach of obtaining these points through iterative methods. As is well known, contraction self-mappings in standard metric spaces yield unique fixed points that can be obtained iteratively. To overcome this limitation, we conduct our study within the framework of generalized MP-metric spaces, utilizing their properties and the broader concept of limits. This enables us to establish our main result: the existence of multiple fixed points that can be iteratively obtained for generalized contraction mappings satisfying specific conditions.